2016
DOI: 10.2528/pierc16062007
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Compact Fractal Ring Based Cylindrical Dielectric Resonator Antenna for Ultra Wideband Application

Abstract: This paper presents a novel compact Koch snowflake fractal ring based Dielectric Resonator Antenna (DRA) for ultra wideband application. Firstly, Koch snowflake fractal geometry is implemented on the conventional Cylindrical Dielectric Resonator Antenna (CDRA). Further, the performance of the DRA is enhanced by fractal ring created on the snowflake geometry. With the application of the fractal and the fractal ring geometry, the Q-factor of DRA is reduced, thus the bandwidth of DRA is increased. The proposed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…The following table 5 summarizes the comparison about the performance of different DRAs designs. Taking into account that the frequencies of the fractal DRAs [4] and S-DRA in [16] are in the high band range (> 6 GHz), it can be observed that the proposed S-DRAs have reduced size and volume (smaller up to 85%) but still remarkable BW and gain G.…”
Section: B Dra Measurements and Experimental Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The following table 5 summarizes the comparison about the performance of different DRAs designs. Taking into account that the frequencies of the fractal DRAs [4] and S-DRA in [16] are in the high band range (> 6 GHz), it can be observed that the proposed S-DRAs have reduced size and volume (smaller up to 85%) but still remarkable BW and gain G.…”
Section: B Dra Measurements and Experimental Resultsmentioning
confidence: 99%
“…A first attempt to select low ε r materials suitable for microwave range applications was proposed by Kumar and Gupta [3], which evaluated several dielectric materials, such as different type of Rogers. Other authors proposed the dielectric material FR4 [4]- [6]. Indeed, as pointed out by the same authors in [4]- [6], the proposed 3D fractal DRAs were manufactured by means of traditional subtractive technologies and a final stack assembly of FR4 disks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore; it is very easy to fabricate. Some other DR‐based fractal geometries are also available in literature such as probe fed four element CDRA array, Sierpinski carpet geometry‐based fractal DRA, Koch snowflake fractal ring DRA, and Fibonacci series‐based CDRA . From abovementioned literature, it can be understood that it is very easy to obtain wider impedance bandwidth in fractal DRA but, its fabrication is highly complex.…”
Section: Introductionmentioning
confidence: 99%
“…Elsheakh and Abdallah [10] proposed an ultrawide bandwidth monopole antenna for DVB-T and wireless applications operating from 4-10.6 GHz with 85.71% bandwidth. Sankaranarayanan et al [11] proposed a novel compact cylindrical dielectric resonator antenna with fractal ring in 4.7-12.4 GHz with 90% bandwidth.…”
Section: Introductionmentioning
confidence: 99%